1991
DOI: 10.3171/jns.1991.75.6.0874
|View full text |Cite
|
Sign up to set email alerts
|

A clinicopathological study of dissecting aneurysms of the intracranial vertebral artery

Abstract: Five autopsied cases of dissecting aneurysms of the intracranial vertebral artery are reported and the literature is reviewed to clarify the clinicopathological correlations. In an autopsy series of 110 patients with subarachnoid hemorrhage (SAH), the incidence of this entity was 4.5%, with all five cases progressing rapidly to death from massive SAH. Cases of intracranial vertebral dissection can be divided clearly into two groups based on the clinical and pathological features. In the first group, the dissec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
126
1
9

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(140 citation statements)
references
References 18 publications
4
126
1
9
Order By: Relevance
“…16) However, this explanation did not always agree with all clinicopathological features of dissecting aneurysms. 11) The main mechanism for the occurrence of artery dissection may be sudden widely spread disruption of the internal elastic lamina of the vessel wall. 7) In all cases, hemodynamic stress is the primary factor causing degeneration of the internal elastic lamina.…”
Section: Discussionmentioning
confidence: 99%
“…16) However, this explanation did not always agree with all clinicopathological features of dissecting aneurysms. 11) The main mechanism for the occurrence of artery dissection may be sudden widely spread disruption of the internal elastic lamina of the vessel wall. 7) In all cases, hemodynamic stress is the primary factor causing degeneration of the internal elastic lamina.…”
Section: Discussionmentioning
confidence: 99%
“…Na quase totalidade das dissecções das artérias vertebrais o hematoma intramural forma-se entre a lâmina elástica interna e a camada média. Raramente a dissecção envolve a camada subadventícia e, quando isto acontece, pode ocorrer ruptura para o espaço subaracnoideo resultando em HSA 2,[4][5][6][7][8][9][10][11][12][13] . Segundo Yamaura 10 , 28% dos aneurismas da circulação posterior, que evoluem com HSA, são lesões aneurismáticas dissecantes.…”
Section: Discussionunclassified
“…O primeiro relato de lesão dissecante arterial é do ano de 1915 7 .Em revisão da literatura de 1924 a 1983 1 , foi observado HSA através de punção lombar em apenas 7 dos 36 casos, não havendo referência de traumatismo em nenhum destes. Outros autores relatam, com freqüência pouco maior, casos de dissecção da artéria vertebral associado com HSA [2][3][4][5][6][8][9][10][11][12][13] , embora não haja, em nenhum deles, associação com traumatismo crâ-nio-cervical. Do ponto de vista angiográfico, essas lesões passaram a ser identificadas a partir de 1959 através de sinais como: retenção de meio de contraste 14 , sinal do duplo lúmen 15 , sinal da roseta 16 e sinal do barbante ("string sign") 17 .…”
unclassified
“…Some 1-10% of all intracranial non-traumatic SAH are caused by ruptured intracranial dissection, and in children, the rate may be even higher. The majority of hemorrhagic intracranial arterial dissection is located in the posterior circulation most likely reflecting it's structure since histological studies 29) have shown that the intradural vertebral artery has a thin media and adventitia with fewer elastic fibers, so dissections of the intradural vertebral artery are prone to result in SAH, in contrast to dissections of other vessels 1) . Brain stem infarctions and aneurysmal arteries presenting as space occupying lesions are other manifestations.…”
Section: Intracranial Vadsmentioning
confidence: 99%